Phenolics in Citrus hystrix leaves obtained using supercritical carbon dioxide extraction - Bakar, Jamilah; M., Abdulkadir Gadi; Mohamed, Suhaila; Sarker, Md. Zaidul Islam (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
The extraction of phenolics from Citrus hystrix leaf was carried out using supercritical fluid extraction and was optimized using response surface methodology (RSM). The effects of CO2 flow rate, extraction pressure and extraction temperature on yield, total phenolic content and diphenyl-picrylhydrazyl-IC50 were evaluated and compared with ethanol extraction. The extraction pressure was the most significant factor affecting the yield, TPC and DPPH-IC50 of the extracts, followed by CO2 flow rate and the extraction temperature. The optimum conditions of pressure, CO2 flow rate and temperature were at 267 bars, 18 g/min and 50oC, respectively. The yield, TPC and DPPH-IC50 obtained were 5.06%, 116.53 mg GAE/g extract and IC50 of 0.063 mg/ml, respectively. These values were not significantly different (p<0.05) to their predicted values. Better inhibition and TPC were obtained using SFE method whereas higher yield and phenolic acids were obtained in the ethanol extracts.